Relationship between silent brain infarction, periventricular hyperintensity and blood pressure - Kobayashi, Shotai; Yamaguchi, Shuhei; Yamashita, Kazuya; Watanabe, Yuji; Aoyama, Koji; Iijima, Kennich (Japanese Journal of Stroke, 2000)
We studied the relationship between silent cerebral infarction (SBI), periventricular hyperintensity (PVH) and blood pressure. Subjects were 1522 neurologically normal adults without history of stroke (mean age, 57.8±8.4 years) who received the brain chech-up from 1988 through 1998. We divided into 8 groups according to JNC-IV in blood pressure at brain check-up. The abnormality of ECG and family history of stroke increased with severity with hypertension. Incidence of SBI was 15.4% and it increased with age. SBI and PVH were related with the severity of blood pres-sure grading, especially with stage 2 or more. SBI was more related with uncontrolled blood pressure at brain check-up than history of hypertension, whereas PVH was motre related with history of hypertension than blood pressure at brain check-up. These results suggent that there is some different underlying mechanism related with blood pressure between SBI and PVH.